Heavy Metal Contamination in the Aquatic Ecosystem: Toxicity and Its Remediation Using Eco-Friendly Approaches - Veer Singh; Nidhi Singh; Sachchida Nand Rai; Ashish Kumar; Anurag Kumar Singh; Mohan P. Singh; Ansuman Sahoo; Shashank Shekhar; Emanuel Vamanu; Vishal Mishra (Toxics, 2023)
Urbanization and industrialization are responsible for environmental contamination in the air, water, and soil. These activities also generate large amounts of heavy metal ions in the environment, and these contaminants cause various types of health issues in humans and other animals. Hexavalent chromium, lead, and cadmium are toxic heavy metal ions that come into the environment through several industrial processes, such as tanning, electroplating, coal mining, agricultural activities, the steel industry, and chrome plating. Several physical and chemical methods are generally used for the heavy metal decontamination of wastewater. These methods have some disadvantages, including the generation of secondary toxic sludge and high operational costs. Hence, there is a need to develop a cost-effective and eco-friendly method for the removal of heavy metal ions from polluted areas. Biological methods are generally considered eco-friendly and cost-effective. This review focuses on heavy metal contamination, its toxicity, and eco-friendly approaches for the removal of heavy metals from contaminated sites.